2018
DOI: 10.1021/jacs.8b11547
|View full text |Cite
|
Sign up to set email alerts
|

Direct Asymmetric Hydrogenation of N-Methyl and N-Alkyl Imines with an Ir(III)H Catalyst

Abstract: A novel cationic [IrH(THF)(P,N)(imine)] [BArF] catalyst containing a P-stereogenic MaxPHOX ligand is described for the direct asymmetric hydrogenation of N-methyl and N-alkyl imines. This is the first catalytic system to attain high enantioselectivity (up to 94% ee) in this type of transformation. The labile THF ligand allows for effective activation and reactivity, even at low temperatures. DFT calculations allowed the rationalization of the stereochemical course of the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 28 publications
3
36
0
Order By: Relevance
“…To demonstrate that, we moved to perform the asymmetric hydrogenation of the homoallylic alcohols 3,w hich are considered minimally functionalized olefins. [29] During the last decade our group has developed several modular P-stereogenic chiral ligands [30] that have proven to be excellent precursors of chiral catalysts.Although our iridium-P, NM axPHOX [31] family of catalysts (6)h ave been successfully applied to the asymmetric hydrogenation of cyclic enamides, [31a] aryl and alkyl imines, [32] and minimally functionalized olefins, [33] including 2-aryl N-allyl phthalimides, [34] we found that in this particular case,u sing 3a as model substrate,[((4S,5S)-Cy 2 -Ubaphox)Ir(COD)]BAr F 4 (7) [35] gave the best results.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…To demonstrate that, we moved to perform the asymmetric hydrogenation of the homoallylic alcohols 3,w hich are considered minimally functionalized olefins. [29] During the last decade our group has developed several modular P-stereogenic chiral ligands [30] that have proven to be excellent precursors of chiral catalysts.Although our iridium-P, NM axPHOX [31] family of catalysts (6)h ave been successfully applied to the asymmetric hydrogenation of cyclic enamides, [31a] aryl and alkyl imines, [32] and minimally functionalized olefins, [33] including 2-aryl N-allyl phthalimides, [34] we found that in this particular case,u sing 3a as model substrate,[((4S,5S)-Cy 2 -Ubaphox)Ir(COD)]BAr F 4 (7) [35] gave the best results.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…63b Interestingly, a recent application of a P( t Bu)Me/oxazoline ligand in the iridium-catalysed hydrogenation of N-alkyl imines suggests that P-stereogenic phosphines also give stiff conformations in the presence of an external rigidifying element, in this case, a cyclometalated benzimine. 64 Overall, the above discussion shows that the conformational issues of P-stereogenic diphosphines play a pivotal role in enantiodiscrimination. Before extending it to tridentate ligands, the synthetic protocols for P-stereogenic building blocks are recapitulated in the next section.…”
Section: Diphosphines With Larger Chelatesmentioning
confidence: 91%
“…Inspired by the hydrogenation of polar C=N double bonds using Ir III monohydride catalysts by Verdaguer and co‐workers, we decided to investigate the asymmetric C=O hydrogenation of trifluoroacetophenones using rhodium(III) monohydride systems . The scope of available discrete precatalysts was expanded by preparing structurally similar dinuclear rhodium(III) complexes, albeit with Josiphos‐type ligands formally replacing BINAP and SEGPHOS (Scheme a).…”
Section: Methodsmentioning
confidence: 99%
“…[25][26][27] Inspired by the hydrogenationo fp olar C=Nd ouble bonds using Ir III monohydride catalysts by Verdaguer and co-workers, we decided to investigate the asymmetric C=Oh ydrogenation of trifluoroacetophenones using rhodium(III) monohydride systems. [28] The scope of availabled iscrete precatalysts was expanded by preparing structurally similard inuclear rhodium(III) complexes,a lbeit with Josiphos-type ligandsf ormally replacing BINAP and SEGPHOS (Scheme 2a). The synthesis wasc arried out by adding 10 equivalents of HCl in diethyle ther to am ixture of [RhCl(cod)] 2 and 2.05 equivalents of the corresponding chiral ligand in toluene.…”
mentioning
confidence: 99%